THE EFFECTIVENESS OF LAW ENFORCEMENT IN COMBATING FOOD HOARDING CRIMES IN INDONESIA - Erma Rusdiana (UNEJ e-Proceeding, 2017)
Indonesia already has legal instruments related to storing and hoarding staple food: Law No.18 of 2012 on Food and Law No. 7 of 2014 on Trade. Repressive and preventive efforts havebeen carried out to combat this problem. However, it is far from what expected resulted inthe frequent occurrences of food hoarding to date. The condition raises questions on how tomake an effective law enforcement in preventing recurring food hoarding in Indonesia. Toknow the effectiveness of law enforcement as an effort to overcome the stockpiling of thebasic commodity, the theory of legal system is used. From the study conducted, it is proventhat the law enforcement of food hoarding is still ineffective. In addition, the Trade MinisterRegulation (Permendag), as mandated by Article 53 of Law No.18 of 2001., has yet to issuethe technical regulations which contribute to the failing in the substance of Food Law.Moreover, it is necessary to limit the prohibited number/quantity of staple food to store orhoard through government stipulation. From the structural side, there exists a sectoral egowithin institutions having authority on food security. Therefore, to establish a strong nationalfood institution which has a cross-sectoral authority is urgently required. The lack of controlfrom the society in the form of community participation in combating food hoarding crimehas more or less contributed to the ineffectiveness of law enforcement.